Filsafat Pendidikan Islam Ibnu Khaldun dan Tantangan Moderasi Beragama di Era Disrupsi - Rama Putra Gema Marulloh; Mukhsin Achmad (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The era of digital disruption presents serious challenges to religious moderation, particularly through the massive flow of religious information, the weakening of scholarly authority, and the growing tendency toward instant and partial religious understanding. These conditions contribute to the rise of rigid, intolerant, and extremism-prone religious attitudes, thereby necessitating a philosophical foundation of Islamic education capable of shaping rational and contextual religious thinking. This study focuses on the philosophy of Islamic education developed by Ibn Khaldun and its relevance in strengthening the values of religious moderation in the era of disruption. This research aims to analyze Ibn Khaldun’s philosophy of Islamic education, examine religious moderation from the perspective of Islamic education, and explain the relevance of Ibn Khaldun’s educational thought in reinforcing the values of religious moderation amid the challenges of the disruptive era. The study employs a qualitative approach using library research. Data are obtained from primary sources, namely Ibn Khaldun’s Muqaddimah, and secondary sources consisting of relevant scholarly books and journal articles, which are analyzed using content analysis techniques. The findings indicate that Ibn Khaldun’s educational thought through its emphasis on the development of reason, the principle of gradual learning (tadarruj), and the rejection of repressive educational practices has strategic relevance in constructing a humanistic, critical, and moderate Islamic education. The integration of this thought can serve as an epistemological and pedagogical foundation for strengthening religious moderation, making it more adaptive to social dynamics and the challenges of the era of disruption.